THE ROLE OF STUDENTS IN RESPONDING TO POLITICAL PARTY PROBLEMS IN GENERAL ELECTIONS IN INDONESIA - Zainul Djumadin (Jurnal Scientia, 2022)
Students, as agents of social change, are expected to make a positive contribution in responding to and overcoming various obstacles faced by political parties during the general election process. This research aims to explore the role of students in facing challenges and problems involving political parties in the context of general elections in Indonesia. This research method involves qualitative analysis of primary and secondary data, including interviews with active students, literature analysis, and case studies related to political parties in previous general elections. The research results show that students play a significant role in responding to and shaping political dynamics, especially in the context of General Election (Election). Students can make positive contributions through critical analysis of political party programs, direct participation in political activities, and promotion of the values of integrity and a clear political vision. Their awareness of the diversity of political views is also a key factor in building unity in a multicultural society. The research results also highlight the importance of students' readiness to face the world of politics, with a deep understanding of political issues, critical assessment of political arguments, and advocacy for honesty as key points in strengthening students' role in building a healthier and more democratic political environment.